2003
DOI: 10.1093/ije/dyg154
|View full text |Cite
|
Sign up to set email alerts
|

Child mortality, socioeconomic position, and one-parent families: independent associations and variation by age and cause of death

Abstract: There does not appear to be notable variation in relative risk terms of socioeconomic differences in child mortality by age or cause of death. Any association of one-parent families with child mortality is due to associated low socioeconomic position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
65
1
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(87 citation statements)
references
References 21 publications
2
65
1
4
Order By: Relevance
“…The earnings of parents seem to have no effect above and beyond education, and there is also no or minor impact of age or marital status of parents. Existing similar studies, based on smaller data sets for other countries, have not shown such a clear relationship between parental education and survival from childhood cancer, 2,5,7,26 but our results are in line with those from a recent, large Korean study. 9 No earlier investigation has addressed the possible importance of siblings.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…The earnings of parents seem to have no effect above and beyond education, and there is also no or minor impact of age or marital status of parents. Existing similar studies, based on smaller data sets for other countries, have not shown such a clear relationship between parental education and survival from childhood cancer, 2,5,7,26 but our results are in line with those from a recent, large Korean study. 9 No earlier investigation has addressed the possible importance of siblings.…”
supporting
confidence: 91%
“…2 Number of children in the respective categories. 3 Percentage of children in the respective categories.…”
Section: Descriptive Statisticsmentioning
confidence: 99%
See 2 more Smart Citations
“…47,[95][96][97][98][99][100] This inverse association appears to be persistent across time, with some evidence of a steepening of the socioeconomic gradient in recent decades in the United States. 101 Furthermore, the relationship appears to hold regardless of whether socioeconomic status is delineated at an individual level, using measures such as income, social class or parental education, or at a more aggregated level using national or regional data on socioeconomic conditions.…”
Section: Socio-economic Statusmentioning
confidence: 99%